Pengembangan Program Ekstrakurikuler Kreatif dan Inovatif untuk Meningkatkan Minat Belajar Siswa di Madrasah Tsanawiyah: Development of Creative and Innovative Extracurricular Programs to Enhance Students' Learning Interest in Madrasah Tsanawiyah - Hadian Akbar (Epistemic: Jurnal Ilmiah Pendidikan, 2024)
This study explores effective strategies for developing extracurricular activities aimed at enhancing students' learning interest within the context of Indonesian education. Utilizing a qualitative research methodology, data were gathered through interviews and direct observations in the field. The findings reveal that creative and innovative extracurricular programs have a positive impact on students' learning interest by offering opportunities to explore their diverse interests and talents. Furthermore, these programs cultivate a sense of belonging and engagement among students, which significantly contributes to their overall academic and personal development. The study underscores the importance of meticulous planning, implementation, ongoing monitoring, and regular evaluation in achieving the desired educational outcomes. By aligning extracurricular activities with students' interests and providing diverse opportunities for skill development, schools can foster a more holistic educational experience that integrates both academic and non-academic growth. This research emphasizes the need for educational institutions to prioritize and continually enhance their extracurricular offerings to fully realize students' potential and improve the overall quality of the learning experience.